PENGARUH KOMPETENSI MANAJERIAL KEPALA SEKOLAH TERHADAP KINERJA GURU BAHASA INDONESIA SMA DI KABUPATEN SLEMAN (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
This research was conducted to find out whether managerial competence of High School principals has influence on the performance of Indonesian High School teachers in Sleman regency.The data was collected using measurement tools in the form of instruments with High School Indonesian teachers in Sleman regency as the respondents. The population of Indonesian teachers of Sleman regency is 80 teachers. Yet, the researcher took 30 teachers as the sample. The data which had been collected was analized by using SPSS version 16. The analysis tecnique was multiple regression formula followed by partial correlation.The result of the research showed that principals’ competencies of : planning, organization, direction, and supervision has significant influence on the performance of Indonesian High School teachers, contributed effectively 76,429%. The effective contribution of the competence of planning is 43,36%, the effective contribution of the competence of organization is 5,88%, the effective contribution of the competence of direction is 11,17%, and the effective contribution of the competence of supervision is 16,07%. It meant that there was another influence as much as 23,50 %. Based of the calculation of the contribution, that competence of planning had the biggest effective contribution on the performance of Indonesian High School teachers.